The Influence of Kahoot Application on Students’ Grammar Achievement in Senior High School - Ursya Tiara Khawas; Endang Mastuti Rahayu; Eliasanti Agustina (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The present study examined whether the Kahoot application influenced the grammar proficiency of eleventh-grade students at SMA Wachid Hasyim 2 Taman. Contextual grammar is crucial in the writing learning process; however, students frequently struggle with writing tasks, largely due to insufficient grammar knowledge. This paper employed a quantitative methodology with a true experimental design. Pre-test and post-test were utilized to evaluate the data. The sample comprised 280 eleventh-grade students from SMA Wachid Hasyim 2 Taman. Cluster random sampling was employed to generate the experimental and control groups. The researcher designated XI-F1 as the experimental group, the Kahoot application was used to provide instruction, while XI-F2 served as the control group, taught using traditional paper-based methods. The data analysis was conducted using an independent sample t-test in SPSS 19. A subjective test was also conducted to measure the students’ grammar skills in the form of creating an analytical exposition text. The findings indicated that the significance (2-tailed) of 0.000 is less than 0.05 (0.000 < 0.05), leading to the acceptance of the alternative hypothesis (Ha). Therefore, it can be concluded that the Kahoot application has a positive and significant influence on eleventh-grade students’ grammar proficiency at SMA Wachid Hasyim 2 Taman. The integration of Kahoot as an interactive and gamified learning tool has the potential to serve as an effective strategy to improve students’ grammar mastery.